2018
DOI: 10.1093/jmt/thy004
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Single Electronic Music Improvisation Session on the Pain of Adults with Sickle Cell Disease: A Mixed Methods Pilot Study

Abstract: Preliminary findings were promising and support the need for additional studies evaluating improvisational music therapy interventions for acute pain management in adults with SCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…In our prior three-arm randomized controlled trial comparing 1) music therapy, 2) music listening, and 3) no music (control), 20 we found that participants with SCD who received a single 20-minute electronic music improvisation session with a music therapist reported significant improvements in pain intensity and mood compared to a control group, whereas participants who received music listening only reported improvements in mood. Qualitative data from this study supported the acceptability and feasibility of a single music therapy intervention for addressing acute pain during an acute care clinic visit.…”
Section: Introductionmentioning
confidence: 91%
“…In our prior three-arm randomized controlled trial comparing 1) music therapy, 2) music listening, and 3) no music (control), 20 we found that participants with SCD who received a single 20-minute electronic music improvisation session with a music therapist reported significant improvements in pain intensity and mood compared to a control group, whereas participants who received music listening only reported improvements in mood. Qualitative data from this study supported the acceptability and feasibility of a single music therapy intervention for addressing acute pain during an acute care clinic visit.…”
Section: Introductionmentioning
confidence: 91%
“…Beyond pharmacologic measures, interventions such as cognitive behavioral therapy, acupuncture, mindfulness, and yoga have demonstrated effectiveness in pain management for individuals with SCD (Mahmood et al, 2020;Moody et al, 2017;Simmons et al, 2019). Distraction from pain through participation in music and virtual reality are also helpful to decreasing pain (Diaz-Hennessy & O'Shea, 2019;Rodgers-Melnick et al, 2018). In fact, researchers have determined that listening to music carries benefits beyond distraction from pain such as regulating mood, focusing attention on studies, relaxing, and connecting with others (Solodiuk et al, 2020).…”
Section: Pain Managementmentioning
confidence: 99%
“…Transfusion is carried out using simple transfusion or exchange transfusion. 82 Rodgers-Melnick et al 105 revealed that standard care and 20 minutes of electronic music improvisation with a board-certified music therapist improved visual analogue scale of pain intensity of SCD patients compared to control using a three-group mixed methods intervention designed study. A retrospective review showed 13 SCD patients who received inpatient acupuncture treatment for acute VOC revealed a reduction in reported pain score immediately after the acupuncture treatment.…”
Section: Current Treatment Of Pain In Scdmentioning
confidence: 99%
“…106 These and other modalities, such as transcutaneous electrical nerve stimulation (TENS), heat, cold and vibration, relaxation, distraction, massage, music, guided imagery, self-hypnosis, self-motivation, acupuncture and biofeedback have been used in controlling pain in SCD; however, there are no controlled clinical studies to support their use. 10,105,[107][108][109][110] Possible targets of pain treatment of SCD and future possibility. Many pharmacological treatments targeting one or more of the mechanisms that contribute to the pain relief or the disease process of SCD are being explored in clinical trials.…”
Section: Current Treatment Of Pain In Scdmentioning
confidence: 99%